The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1038/sj.gene.6364102
|View full text |Cite
|
Sign up to set email alerts
|

Deficient IL-12p70 secretion by dendritic cells based on IL12B promoter genotype

Abstract: Interleukin-12 (IL-12), a heterodimeric cytokine, is important in the generation of a Th1-biased immune response. Several polymorphisms have been described in IL12B, the gene encoding the p40 subunit of IL-12. A bi-allelic polymorphism within the IL12B promoter region has been reported to show association with diseases as diverse as severe childhood asthma and fatal cerebral malaria. In order to define the molecular basis for these disease associations, we investigated the secretion of IL-12 by human monocyte-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 21 publications
6
50
1
Order By: Relevance
“…In general, there is a disagreement about the effect of IL12Bpro polymorphism on the inducible IL-12p40 production. The investigations of Müller-Berghaus et al [24] showed that there were no significant differences in IL-12p40 production between IL12Bpro-1 homozygotes, heterozygotes and 2.2 homozygotes, realized by monocyte-derived dendritic cells after stimulation with CD40L. By contrast, Morahan et al [9] revealed that heterozygosity in the IL12B promoter sequence reduced IL-12p40 mRNA synthesis in PBMC from asthmatic children.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In general, there is a disagreement about the effect of IL12Bpro polymorphism on the inducible IL-12p40 production. The investigations of Müller-Berghaus et al [24] showed that there were no significant differences in IL-12p40 production between IL12Bpro-1 homozygotes, heterozygotes and 2.2 homozygotes, realized by monocyte-derived dendritic cells after stimulation with CD40L. By contrast, Morahan et al [9] revealed that heterozygosity in the IL12B promoter sequence reduced IL-12p40 mRNA synthesis in PBMC from asthmatic children.…”
Section: Discussionmentioning
confidence: 91%
“…The sequence of the primer specific for the CTCTAA allele, marked as IL12Bpro-1 was 5'-TGT CTC CGA GAG AGG CTC TAA-3'; and that for the GC allele marked as IL12Bpro-2 was 5'-TGT CTC CGA GAG AGG GCT GT-3'. The generic 3' primer used for the amplification reactions was 5'-TGG AGG AAG TGG TTC TCG TAC-3' [24]. The cycling parameters were: an initial denaturation step of 15 min at 95ºC, 30 cycles of 30 sec at 95ºC, 30 sec at 65ºC, and 30 sec at 72ºC, with a final extension step of 7 min at 72ºC.…”
Section: Genomic Dna Isolation and Genotypingmentioning
confidence: 99%
“…We suppose that a reason for our contrary findings might be the different type of IL-12B expression in isolated monocytes and PBMC. Muller-Berghaus et al 20 recently reported the effect of IL-12Bpro on dendritic cell IL-12 production and considered that the effects of the IL-12Bpro alleles may vary according to cell type and stimulus. Moreover, our results indicated that the production of IL-12p40 strongly depends on the stimuli used.…”
Section: Resultsmentioning
confidence: 99%
“…A 4-bp insertion in the promoter region of IL-12B (IL-12Bpro; rs17860508) has been shown to decrease the amount of IL-12p70 secreted by human monocyte-derived dendritic cells in vitro. 7 A further polymorphism present within the 3 0 UTR of the IL-12B gene (rs3212227), reflecting an A to C nucleotide substitution at position 1188, has been associated with various autoimmune diseases including type 1 diabetes, 8 multiple sclerosis 9 and psoriasis. 10 The IL-12 p40 subunit can also form heterodimers with p19 resulting in formation of IL-23.…”
Section: Interleukin (Il)-17a Is the Prototypic Cytokine Produced By Cd4mentioning
confidence: 99%